File Sharing Techniques in Digital world - Kanimozhi, J; V Swathilakshmi, V Swathilakshmi; Aravindh, S; Hemachandira, S; Dinesh, M (International Journal of Computer Sciences and Engineering, 2020)
File sharing is the exchange of computerized data for example computer programs, audio or video records, documents or electronic books over the web with others. There are many ways of file sharing. Some of them are, Peer-toPeer, Cloud storage service and Removable storage media. Peer-to-peer involves computer hardware and software to communicate without the need for a central server. Cloud storage service is like peer-to-peer file sharing. Notwithstanding, rather than sending the document straightforwardly to the others, the record is sent to a server that stores the record. When the document is put away in the cloud (on the web), we can allow different clients can download it by providing them the link of file. Removable storage media is vast different from other two ways. File sharing is done physically by the user with the help of any storage devices. In this work, we are going to see the different file sharing techniques used in this digital world.